2015
DOI: 10.1111/age.12276
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of non-synonymous SNPs of the porcineSERPINA6gene as potential causal variants for a QTL affecting plasma cortisol levels on SSC7

Abstract: Recently, the SERPINA6 gene encoding corticosteroid-binding globulin (CBG) has been proposed as a candidate gene for a quantitative trait locus (QTL) affecting cortisol level on pig chromosome 7. The QTL was repeatedly detected in different lines, including a Piétrain × (German Landrace × German Large White) cross (PiF1) and purebred German Landrace (LR). In this study, we investigated whether the known non-synonymous polymorphisms c.44G>T, c.622C>T, c.770C>T, c.793G>A, c.832G>A and c.919G>A of SERPINA6 are su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
(40 reference statements)
2
5
0
Order By: Relevance
“…The significant additive QTL for CORT_105 was detected on SSC7, and the corticosteroid-binding globulin (CBG, also known as SERPINA6) gene was regarded as a positional candidate gene in the QTL region. The SERPINA6 gene encodes CBG affecting cortisol-binding capacity and SNPs at the SERPINA6 locus influence plasma cortisol levels in humans [42] and pigs [39,40,41]. Our results supported the finding that the SERPINA6 gene would be a positional candidate gene for CORT_105.…”
Section: Running Headsupporting
confidence: 86%
See 1 more Smart Citation
“…The significant additive QTL for CORT_105 was detected on SSC7, and the corticosteroid-binding globulin (CBG, also known as SERPINA6) gene was regarded as a positional candidate gene in the QTL region. The SERPINA6 gene encodes CBG affecting cortisol-binding capacity and SNPs at the SERPINA6 locus influence plasma cortisol levels in humans [42] and pigs [39,40,41]. Our results supported the finding that the SERPINA6 gene would be a positional candidate gene for CORT_105.…”
Section: Running Headsupporting
confidence: 86%
“…GWAS detected a total of six significant additive QTL and three significant nonadditive QTL, as well as a positional candidate gene by genome-wide QTL mapping, which was previously only reported in the SSC7 region of CORT_105 specimens in different breeds [39,40,41]. The significant additive QTL for CORT_105 was detected on SSC7, and the corticosteroid-binding globulin (CBG, also known as SERPINA6) gene was regarded as a positional candidate gene in the QTL region.…”
Section: Running Headmentioning
confidence: 85%
“…Allelic expression imbalance has also been analyzed for several genes thought to affect pig meat quality and fatness traits. Deviations between allelic transcript levels were detected for ADRB2 in l. dorsi muscle [ 24 ], SERPINA6 and APOA2 in liver [ 25 , 26 ] but not for ADIPOQ in skeletal muscles and backfat [ 27 ]. Our study analyzed ASE of four functional candidate genes encoding transcription factors ( PPARA, PPARG, SREBF1 ) and a coactivator of multiple transcription factors ( PPARGC1A ) using pyrosequencing as an accurate and sensitive means of quantifying allelic transcript proportions [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that the substitution Gly307Arg, originating from domestic pigs [ 115 ], increases CBG capacity and decreases CBG affinity for cortisol. However, the amino acid substitutions do not fully explain the QTL in any of the populations where the QTL has been detected [ 114 , 116 , 117 ]. Apart from coding variation, SERPINA6 function is apparently diversified by regulatory variation [ 114 , 117 ].…”
Section: Genetics Of Stress Responsementioning
confidence: 99%
“…However, the amino acid substitutions do not fully explain the QTL in any of the populations where the QTL has been detected [ 114 , 116 , 117 ]. Apart from coding variation, SERPINA6 function is apparently diversified by regulatory variation [ 114 , 117 ]. Thus, the causal effect might result from an interaction of the regulatory with the coding variation.…”
Section: Genetics Of Stress Responsementioning
confidence: 99%